Coordinated Control Strategy for Hybrid Black Start with LCC HVDC System and Auxiliary Synchronous Generator - Yong Li; Hongtao Wang; Huiting Yang (CSEE Journal of Power and Energy Systems)
Inverter-based resources (IBRs) are expected to support black start in case of blackout events, as they can significantly speed up restoration process. This paper proposes a coordinated control scheme to improve frequency and voltage stability for hybrid black start resource (HBSR) participated restoration. HBSR includes a line-commutated converter (LCC)-based high-voltage direct-current (HVDC) system and a self-starting generator. In the proposed scheme, outputs of different resources are controlled in a coordinated manner to suppress disturbances caused by inrush loads, where an active power error controller (PEC) and a reactive power error controller (QEC) are developed based on an analytical model. The analytical model calculates desired DC current reference considering the coupling effects between active power and reactive power under weak grid conditions. PEC is designed as a multi-variable system, which regulates active power of the LCC HVDC line so that frequency variation can be damped and eliminated properly. QEC observes reactive power related security margin and regulates the inverter extinction angle to reduce the risk of commutation failure. Simulations are executed on an HBSR integrated test network based on the CIGRE Benchmark model. Results show that in HBSR dominated black start, frequency deviations and voltage fluctuations can be suppressed more speedily and stably by the proposed control method, and the extinction angle is adapted for more secure commutation in case of insufficient reactive power.